ANALISIS YURIDIS PERLINDUNGAN PENGETAHUAN TRADISIONAL DAN EKSPRESI BUDAYA TRADISIONAL DALAM PEMBUATAN ULOS BATAK TOBA DI KABUPATEN TOBASA - SARIAMAN MARPAUNG (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. Jelly Leviza, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHum The objective of the research was to find out the system of protection for traditional knowledge and traditional culture expression in making Batak Toba ulos in Tobasa (Toba Samosir) Regency. Central government and local government play an important role in socializing understanding the importance of protection for knowledge to ulos craftsmen in Tobasa Regency. From its definition and scope, traditional knowledge is closely related to the ownership and characteristics of ulos communal ownership. It also reflects the concept of ulos legal ownership. It becomes new problems in Indonesia because Indonesia has not had specific regulation which regulates Protection for Traditional Knowledge so far. The research used juridical normative and descriptive analytic method by analyzing legal provisions such as Law No. 28/2014 on Copyright, Law No. 13/2016 on Patent Rights, and Law No. 5/2017 on Advancing Culture. It was done in Toba Samosir Regency.Keywords: Batak Toba, Ulos, Legal Protection, Traditional Knowledge, Traditional Culture Expression